Mengintegrasikan Dakwah Budaya dan Struktural dalam Pengembangan Masyarakat: Kerangka Transdisipliner untuk Transformasi Sosial Islam: Integrating Cultural and Structural Da’wah in Community Development: A Transdisciplinary Framework for Islamic Social Transformation - Adelia Mustika Putri Suwarno; Salsabilla Zahwa Naura; Adelia Tria Lestari; Ali Hasan Siswanto (Litera Academica Publishing, 2025)
This study addresses the epistemological fragmentation between cultural and structural da’wah that undermines the transformative mission of Islamic propagation in contemporary Muslim societies. The main research question explores how cultural values, institutional structures, and community empowerment can be integrated into a transdisciplinary framework for sustainable Islamic social transformation. Using a qualitative exploratory design grounded in a constructivist paradigm, the study employs a transdisciplinary approach that merges community development theory, Islamic communication, and public policy analysis. Data were gathered through literature mapping of Scopus-indexed publications, document analysis of Islamic development programs, and expert interviews with da’wah scholars and practitioners. The findings indicate that the dichotomy between cultural and structural da’wah has weakened the link between spiritual values and institutional policies. Through a community development approach, da’wah can shift from a normative religious activity to a transformative social movement. The study introduces the Integrative Da’wah Framework, which bridges local wisdom, institutional support, and digital engagement, providing a novel epistemological basis for reconstructing Islamic social sciences and promoting participatory, inclusive social policies in the digital era.